Evaluating loggerhead sea turtle (Caretta caretta) bycatch in the small-scale fisheries of Cabo Verde - Martins, Samir (2022)
The incidental or target capture of sea turtles by small-scale fisheries (SSF) has been receiving increasing attention in recent years due to its high impact. Here, we evaluated the impact of the SSF on sea turtles in Cabo Verde, which hosts the largest rookery of the endangered Eastern Atlantic loggerhead turtle (Caretta caretta) population. This is the most comprehensive study evaluating the impact of SSF on sea turtles in the Cabo Verde Archipelago involving more than 85% of boats and more than 20% of the fishermen registered in the archipelago. Between the years of 2011 and 2014, 763 artisanal fishermen were interviewed at all the main ports and fishing communities of seven islands. Artisanal fishermen reported a mean annual capture of 1.5 turtles per boat indicating that a minimum of 1675 sea turtles could be landed per year in this fishing sector alone, with 65% in Santiago Island (which host the country's capital, Praia). Most captures (95.7%) occurred from May to September and coincided with the loggerhead turtle nesting season. These results suggest a severe impact of the SSF on adult loggerheads turtles in Cabo Verde as well as green (Chelonia mydas) and hawksbill (Eretmochelys imbricata) juvenile turtles. To mitigate this impact, measures such as revising the current legislation for fisheries, the supervision and control of landings, especially in the most remote ports of the Archipelago, the regulation of the SSF during the nesting season around the main nesting areas, awareness-raising campaigns, sustainable activities, and alternative sources of income in fishing communities are recommended.